isihcikêwinihk kâkî nâtawihon: Healing Through Ceremony - Bodor, Ralph; Cardinal, Terri; Kopp, Kristina (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2022)
isihcikêwinihk kâkî nâtawihon (Healing through Ceremony) is an audio-visual learning experience created in ceremony and in relationship with knowledge-keepers, wisdom-holders, language speakers, and the survivors of Indian Residential Schools and their descendants. In ceremony and in language, the authors met with 23 knowledge-keepers and Indigenous community members who shared their experiences of “healing through ceremony.” Through protocol and relationship, the knowledge-keepers and Indigenous community members gave permission to the authors to have the teachings and stories recorded and documented. The audio-visual learning experience came to be understood as an experience of kiskinowapahtam – to heal, teach, and learn by watching and doing. The teachings and stories shared in isihcikêwinihk kâkî nâtawihon guide social workers toward understanding how to support Indigenous communities in healing from the legacy of Residential Schools and the lasting intergenerational impacts of colonization. isihcikêwinihk kâkî nâtawihon supports the preservation of Indigenous knowledge regarding healing and ceremony and directly impacts current and future generations through providing this knowledge to social workers serving Indigenous communities. From this teaching experience, the knowledge-keepers, community members, and authors share a collective vision that Indigenous children, families, and communities encounter social workers who understand, honour, and trust the healing that happens in ceremony.